The use of games in teaching English - Usenova, G.; Ganieva, Z. (ILIM hám JÁMIYET, 2018)
The article deals with the methods of using games in the process of teaching foreign languages in elementary schools. The given methods are possible to use on any step of teaching a foreign language. The use of different games at the lesson promotes to the creation of the friendly atmosphere, growth of collective knowledge in the classroom.